Potensi Komposit Serat Bambu Untuk Mengganti Material Kayu Gerobak Ditinjau Dengan Uji Elastisitas - Alhara Yuwanda (Sekolah Tinggi Teknik - PLN, 2017)
Wooden carts have deficiencies of physical properties such as: heavy, easily weathered when exposed to rain, and not attractive. This can be overcome by replacing the polymer composite. In this study the mixture of materials used to make composites is Polyester Resin (Yucalak 157 BQTN-EX), Catalyst, Wax, Bamboo Fiber Apus / Rope. The research that has been done is the composite test with bending and impact test. Based on the test results with the test, the impact and composite strength of the composite is better than the wood commonly used for making cart material. In addition, the strength of bending elasticity and strain on bending test is also quite high. Highest elasticity at 30% bamboo fiber filling. Thus it can be concluded that bamboo composite can be an alternative to wood material on wagon.